2004
DOI: 10.1111/j.1471-4159.2004.02617.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel neuromodulator hydrogen sulfide: an endogenous peroxynitrite ‘scavenger’?

Abstract: Hydrogen sulfide (H 2 S) is a well-known cytotoxic gas. Recently it has been shown to stimulate N-methyl-D-aspartate (NMDA) receptors to enhance long-term potentiation suggesting a novel neuromodulatory role in vivo. Endogenous levels of H 2 S in the brain are reported to range between 10 and 160 lM. Considerably lower H 2 S levels are reported in the brains of Alzheimer's disease (AD) patients, where levels of brain protein nitration (probably mediated by peroxynitrite) are markedly increased. Activation of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
391
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 554 publications
(408 citation statements)
references
References 41 publications
8
391
2
7
Order By: Relevance
“…Hcy induces accumulation of reactive oxygen species (ROS) and stimulates neurotoxicity [43,44] , whereas H 2 S scavenges ROS and protects neurons against oxidative stress [45][46][47][48] . Furthermore, both elevation of Hcy and decrease of H 2 S are detected in the brains of AD patients [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Hcy induces accumulation of reactive oxygen species (ROS) and stimulates neurotoxicity [43,44] , whereas H 2 S scavenges ROS and protects neurons against oxidative stress [45][46][47][48] . Furthermore, both elevation of Hcy and decrease of H 2 S are detected in the brains of AD patients [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptor cell death is an irreversible injury that is caused by various factors, such as reactive oxygen species (ROS) and elevated intracellular concentrations of Ca 2ϩ (40). Because H 2 S protects neurons from oxidative stress (17,18,21), it is possible that H 2 S protects photoreceptor cells from light-induced retinal degeneration. To examine this possibility, we investigated the effect of H 2 S on retinal degeneration caused by exposing the retina to excessive levels of light.…”
Section: H 2 S Protects Retinal Photoreceptor Cells From Light-inducedmentioning
confidence: 99%
“…H 2 S facilitates the nuclear localization of a transcription factor, nuclear factor erythroid 2-related factor 2 (Nrf2), which increases the expression of antioxidants such as thioredoxin and heme-oxygenase1 (20). H 2 S produced by 3MST along with CAT can directly react with several cytotoxic oxidant species in mitochondria to protect cells (18,21).…”
mentioning
confidence: 99%
“…Overproduction of these reactive intermediates would not only damage the bacteria but would damage surrounding tissue, precipitating a further inflammatory response. Inhibition of 'oxidative stress' by inactivating enzymes or the direct 'scavenging' of the oxidant species would be expected to contribute to the many potential anti-inflammatory effects of H 2 S. In vitro experiments have shown that H 2 S generated from sulfide salts (Na 2 S and NaSH) inhibits cellular damage and intracellular protein oxidation induced by HOCl [77,78], ONOO - [79] and • NO [34,80]. NaSH is also reported to scavenge and/or degrade lipid peroxides [81,82] and inhibit the expression and activity of NAD(P)H oxidase [83,84].…”
Section: Antioxidant Activity Of H 2 S?mentioning
confidence: 99%